When individual goal pursuit turns competitive: How we sabotage and coast - HUANG, Szu-chi (Institutional Knowledge at Singapore Management University, 2019)
People working toward individual goals often find themselves surrounded by others who are pursuing similar goals, such as at school, in fitness classes, and through goal-oriented network devices like Fitbit. This research explores when these individual goal pursuits can turn into competitions, why it happens, and the downstream consequences of this pseudo-competition on goal pursuers. We found that people were more likely to treat their goal pursuit as a competition when they were near the end (vs. at the beginning) of their individual goal and thus prioritized relative positional gain (i.e., performing better than others sharing similar pursuits) over making objective progress on their own goal, sabotaging others when they had the opportunity to do so (Studies 1–3B). Further, we provided evidence that certainty of goal attainment at a high (vs. low) level of progress drove this shift in focus, leading to such sabotage behaviors (Studies 3A, 3B). Ironically, success in gaining an upper hand against others in these pseudo-competitions led individuals to subsequently reduce their effort in their own pursuits (Studies 1–5). Six experiments captured a variety of competitive behaviors across different goal domains (selecting games that diminished others’ prospects, selecting difficult questions for fellow students).